Various Factors that Influence the Successful Implementation of School Digitalization Policies - Nurkolis, Nurkolis; Muhdi, Muhdi; Maryant, Maryanto; Kusumaningsih, Widya (KnE Social Sciences, 2024)
School digitalization in Indonesia has been widely implemented in line with the 2020/2021 education transformation policy. Various factors are thought to support the success of digitizing the learning process, school management, and how people work in schools. This research aims to determine various factors that positively influence the successful implementation of school digitalization at Junior High Schools (SMP) and Madrasah Tsanawiyah (MTs). This research uses a quantitative cause-and-effect approach with a questionnaire distributed online. The research was conducted in semester 1 of 2023 with 1088 respondents. Data processing was done using non-parametric Mann-Whitney and Kruskal-Wallis statistics for normal distribution. The research results that consistently show a positive and significant influence are differences in regions and respondent positions. Factors not influencing school digitalization are gender and type of school. Inconsistently influential factors are the respondent’s age, type of school transformation intervention, and school status. Regional differences, which indicate differences in school digitalization policies by local education leaders, positively influence the success of school digitalization. Likewise, the stronger a person’s position in a school in pushing policy, the greater the influence on the quality of school digitalization. Thus, the two factors, namely a person’s position and regional differences, indicating differences in leadership, are recommended to be strengthened to increase the success of implementing school digitalization policies. Keywords: educational transformation, digitalization of learning’ digitalization of management, digitalization of ways of working